Is chronic pain as an autoimmune disease? - Gurmit Singh (Taylor & Francis Group, 2022)
ABSTRACTAutoimmune diseases frequently occur in females, and a parallel sexually dimorphic suffering is observed in individuals who suffer chronic pain. Though perception and environment influence the chronicity of pain, this review illustrates examples of specific, evolutionarily preserved, physiological parameters that may be responsible and differentially contribute to chronic pain and affect treatment outcomes in females and males. In females, the immune system may be continuously "primed," potentially due to the presence of two X chromosomes, each bearing a number of genes involved in immune responsiveness. In the event of nerve injury, declining parity rates could be having repercussions via increased rates of chronic pain or less effectiveness to therapies, which may be associated with a heightened immune cell infiltration into damage-associated sites. Additionally, the female hormone estradiol is both neuroprotective and neurodegenerative, with reproductive cycle- and age-dependent outcomes. There is therefore a need to study neuro-immune-endocrine crosstalk in the context of chronic pain. Autoantibodies have been associated to neural antigens with sensory pathway hyperexcitability in patients, and self-antigens need to be identified by damaged nerves remain to be discovered. Specific T cells release pronociceptive cytokines that directly influence neural firing, and T lymphocytes reactivated by specific antigens may elicit neuroprotective effects by secreting factors that support nerve repair. Modulating immune cells could therefore be a mechanism by which nerve recovery is promoted, with sex-specific outcomes. Investigating neuroimmune homeostasis may inform the selection of specific treatment regimens for females or males and hence may improve chronic pain management by recalibrating the influence of the immune system on the nervous system.